17th IEEE International Multi Topic Conference 2014 2014
DOI: 10.1109/inmic.2014.7096902
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-wideband patch antenna for microwave communications

Abstract: A study of ultra-wideband (UWB) microstrip patch antenna for microwave related applications is presented. According to -10 dB impedance bandwidth criteria, the antenna is able to operate in the frequency range 4.7-17 GHz. The antenna is designed on FR-4 epoxy with thickness 1.6 mm and dielectric constant 4.4. An air gap is used between two dielectrics whereas, inverted patch configuration is employed to achieve ultra-wideband characteristics. From proposed design, an average gain of 10 dBi is observed. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The novelty of the proposed microstrip antenna compared to the other microsrip antenna can be seen in term of its size and obtained bandwidth .As mentioned above the obtained bandwidth of the designed antenna is 7GHz with overall size 2.1* 1.7*0.787 cm . the proposed anetnna can be compared with designed CPW fed X-band antenna (Tripathis and Sigh,2013)and Ultra-Wideband antenna (Rafique et .al ,2014 ), which has 4 GHz and 5.89 GHz bandiwdth with overall size 3*2.5*1.5 cm and 6.2*6.4*2 cm respectivily .It can be concluded that the size of the antenna significantly reduced and the obtained bandwidth improved by ustiliing step loaded structure. The voltage standing wave ratio, which is shown in Figure 4, is below 1.5 within the frequencies 7-14.5 GHz.…”
Section: Simulation Resultsmentioning
confidence: 96%
“…The novelty of the proposed microstrip antenna compared to the other microsrip antenna can be seen in term of its size and obtained bandwidth .As mentioned above the obtained bandwidth of the designed antenna is 7GHz with overall size 2.1* 1.7*0.787 cm . the proposed anetnna can be compared with designed CPW fed X-band antenna (Tripathis and Sigh,2013)and Ultra-Wideband antenna (Rafique et .al ,2014 ), which has 4 GHz and 5.89 GHz bandiwdth with overall size 3*2.5*1.5 cm and 6.2*6.4*2 cm respectivily .It can be concluded that the size of the antenna significantly reduced and the obtained bandwidth improved by ustiliing step loaded structure. The voltage standing wave ratio, which is shown in Figure 4, is below 1.5 within the frequencies 7-14.5 GHz.…”
Section: Simulation Resultsmentioning
confidence: 96%